Festival Citylink Brand Audit and Improvement - Riswandi, Ridwan; Iskandar, Budi Permadi (The Indonesian Journal of Business Administration, 2013)
Festival Citylink (FCL) is a shopping center that using concept mixed-use integration between shopping center, hotels and convention center located in South Bandung area. The problem that faces by Festival Citylink is low on brand equity performance, brand history and the intense of competition. Based on survey result in 2011, Festival Cityink has low in brand awareness, recall and response. The negative perception brand image from predecessor Mollis as shopping center before Festival Citylink. The intense competition among shopping center in Bandung that account for 30 shopping centers. This lead to low market share which reaches only 5% compare to competitors and the average of customer traffic reach only 11.000 visitor/day considered below the company target for 20.000 visitor/day. The conceptual framework is using Customer Based Brand Equity (Keller,2008). The brand audit is done by searching source brand equity from customer and company perspective. From company perspective to find the brand strategy committed by company and from customer perspective to know what customer perception about brand, product and service offered by company. The focus of this final project is to provide solution to increase brand equity Festival Citylink in the midst of competition. the internal and external analysis conduct to find the root cause of the problems. The result shows that there are three problems consist of (1) Brand element considered less effective in create strong, unique and favorable association and low brand performance. (2) The effectiveness and efficiency of integrated marketing communication. (3) Low service environment performance for shopping center. Some recommendation proposed for increasing brand equity consists of the change and maintain brand element that supports for brand equity performance, propose target market and positioning, increase integration marketing communication and improve servicescape to get positive experience and image. Keywords: Shopping Center, CBBE, Brand Equity, Association, Festival Citylink